2015
DOI: 10.1126/scisignal.2005673
|View full text |Cite
|
Sign up to set email alerts
|

Ca 2+ signals regulate mitochondrial metabolism by stimulating CREB-mediated expression of the mitochondrial Ca 2+ uniporter gene MCU

Abstract: Cytosolic Ca2+ signals, generated through the coordinated translocation of Ca2+ across the plasma membrane (PM) and endoplasmic reticulum (ER) membrane, mediate diverse cellular responses. Mitochondrial Ca2+ is important for mitochondrial function and, when cytosolic Ca2+ concentrations become too high, mitochondria function as cellular Ca2+ sinks. By measuring mitochondrial Ca2+ currents, we found that mitochondrial Ca2+ uptake was reduced in chicken DT40 B lymphocytes lacking either the ER-localized inositol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 82 publications
2
95
0
Order By: Relevance
“…35 Therefore, we investigated whether CREB was involved in FUNDC1-induced Fis1 expression. First, we examined whether FUNDC1 regulates CREB phosphorylation in heart, and found that Fundc1 deletion resulted in decreased phosphorylation of CREB at Ser133 (Supplemental Figure 11B and 11C).…”
Section: Resultsmentioning
confidence: 99%
“…35 Therefore, we investigated whether CREB was involved in FUNDC1-induced Fis1 expression. First, we examined whether FUNDC1 regulates CREB phosphorylation in heart, and found that Fundc1 deletion resulted in decreased phosphorylation of CREB at Ser133 (Supplemental Figure 11B and 11C).…”
Section: Resultsmentioning
confidence: 99%
“…Perturbation of [Ca 2+ ] m uptake may lead to cellular bioenergetic crisis (McCormack and Denton, 1990; Shanmughapriya et al, 2015b). To determine the effect of reduced [Ca 2+ ] m uptake, ATP levels in endothelial cells derived from MCUR1 ΔEC and MCU ΔEC mice were examined.…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptional regulation has been shown to occur through the calcium-dependent transcription factor cAMP response-element binding protein, which binds to the MCU promoter 47 . Synaptic activity was shown to repress transcription of Mcu through a calmodulin kinase-dependent mechanism 48 .…”
Section: Additional Layers Of Regulationmentioning
confidence: 99%